Recent summer warming over the western Mediterranean region is unprecedented since medieval times - Büntgen, Ulf; Reinig, Frederick; Verstege, Anne; Piermattei, Alma; Kunz, Marcel; Krusic, Paul; Slavin, Philip; Štěpánek, Petr; Torbenson, Max; del Castillo, Edurne Martinez; Arosio, Tito; Kirdyanov, Alexander; et al. (Global and planetary change, 2024)
Contextualising anthropogenic warming and investigating linkages between past climate variability and human history require high-resolution temperature reconstructions that extend before the period of instrumental measurements. Here, we present maximum latewood density (MXD) measurements of 534 living and relict Pinus uncinata trees from undisturbed upper treeline ecotones in the Spanish central Pyrenees. Spanning the period 1119–2020 CE continuously, our new MXD composite chronology correlates significantly with gridded May–September mean temperatures over the western Mediterranean region (r = 0.76; p ≤ 0.001; 1950–2020 CE). Based on an integrative ensemble approach, our reconstruction reveals unprecedented summer warming since 2003 CE. The coldest and warmest reconstructed temperature anomalies are −3.4 (±1.4) °C in 1258 and 2.6 (±2.2) °C in 2017 (relative to 1961–90). Abrupt summer cooling of −1.5 (±1.0) °C was found after 20 large volcanic eruptions since medieval times. Comparison of our summer temperature reconstruction with newly compiled historical evidence from the Iberian Peninsula suggests a lack of military conflict during or following exceptionally hot or cold summers, as well as a general tendency towards less warfare and more stable wheat prices during warmer periods. Our study demonstrates the importance of updating and refining annually resolved and absolutely dated climate reconstructions to place recent trends and extremes of anthropogenic warming in a long-term context of natural temperature variability, and to better understand how past climate and environmental changes affected ecological and societal systems. [Display omitted] •A total 534 MXD samples from the Pyrenees cover the period 1119–2020 CE continuously.•An integrative ensemble approach was used to improve our highly replicated MXD record.•Recent warming over the western Mediterranean is unprecedented since medieval times.•Abrupt summer cooling of −1.5 °C in the Pyrenees followed large volcanic eruptions.•Less warfare and stable wheat prices in Iberia coincide with periods of warmer climate.